Development of Electronic Student Worksheets Based on The Theory of Conceptual Change in Thermodynamics - Innas Amalia Utami; Syuhendri Syuhendri; Ida Sriyanti (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2022)
The development of valid and practical electronic student worksheets based on the theory of conceptual change in thermodynamics material has been completed. This development research uses the Rowntree development model which consists of three stages, namely the planning stage, the development stage, and the evaluation stage. At the evaluation stage, the researcher used Tessmer's formative evaluation in the form of self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Data collection instruments used expert validation sheets and questionnaires. The results of data analysis at the expert review stage obtained an average expert validation of 4.4 with a very valid category. The average of the student questionnaire sheets in the one-on-one evaluation and small group evaluation phases was 4.4 and 4.5, respectively, with a very practical category. Thus, an electronic student worksheet based on the theory of conceptual change has been successfully developed on valid and practical thermodynamic material. This electronic student worksheet can be used to clarify conceptual understanding and correct thermodynamics misconceptions. Keywords: Development of Electronic Student Worksheets, Overcoming Misconceptions, Physics